Improvement of MRI examination in cerebral thromboembolism - Qaynarbekova Mokhinur; Ablyazov A.A; Zulunov Azizbek (Zien Journals, 2022)
Background Cerebral venous thrombosis (CVT) is a rare disease, and with poor prognosis. Computed tomography (CT) and magnetic resonance imaging (MRI) are the most commonly used image modalities for patients with non-specific neurologic symptoms. We present here a meta-analysis to assess the accuracy of CT and MRI in the differential diagnosis of CVT and cerebral venous sinus thrombosis (CVST). Materials and Methods A comprehensive search of the PubMed, EMBASE, Web of Science, Cochrane Database and Chinese Biomedical (CBM) databases was conducted. In this report, we assess the methodological quality of each article individually and perform a meta-analysis to obtain the summary of the diagnostic accuracy MRI in correctly identifying CVT and CVST. Results Twenty-four eligible articles comprising 48 studies (4,595 cases) were included. The pooled sensitivity for CT–CVT/CT–CVST groups is 0.79 (95% confidence interval,with an area under the curve (AUC) for the summary receiver operating characteristic (SROC) of 0.9314/0.9161
Keywords: quality; Computed tomography; magnetic resonance tomography; intracranial thrombosis